Wild specimens of sand fly phlebotomine Lutzomyia evansi, vector of leishmaniasis, show high abundance of Methylobacterium and natural carriage of Wolbachia and Cardinium types in the midgut microbiome - Vivero, Rafael J. (Sci Rep, 2019)
Phlebotomine sand flies are remarkable vectors of several etiologic agents (virus, bacterial, trypanosomatid Leishmania), posing a heavy health burden for human populations mainly located at developing countries. Their intestinal microbiota is involved in a wide range of biological and physiological processes, and could exclude or facilitate such transmission of pathogens. In this study, we investigated the Eubacterial microbiome from digestive tracts of Lu. evansi adults structure using 16S rRNA gene sequence amplicon high throughput sequencing (Illumina MiSeq) obtained from digestive tracts of Lu. evansi adults. The samples were collected at two locations with high incidence of the disease in humans: peri-urban and forest ecosystems from the department of Sucre, Colombia. 289,068 quality-filtered reads of V4 region of 16S rRNA gene were obtained and clustered into 1,762 operational taxonomic units (OTUs) with 97% similarity. Regarding eubacterial diversity, 14 bacterial phyla and 2 new candidate phyla were found to be consistently associated with the gut microbiome content. Proteobacteria, Firmicutes, and Bacteroidetes were the most abundant phyla in all the samples and the core microbiome was particularly dominated by Methylobacterium genus. Methylobacterium species, are known to have mutualistic relationships with some plants and are involved in shaping the microbial community in the phyllosphere. As a remarkable feature, OTUs classified as Wolbachia spp. were found abundant on peri-urban ecosystem samples, in adult male (OTUs n = 776) and unfed female (OTUs n = 324). Furthermore, our results provide evidence of OTUs classified as Cardinium endosymbiont in relative abundance, notably higher with respect to Wolbachia. The variation in insect gut microbiota may be determined by the environment as also for the type of feeding. Our findings increase the richness of the microbiota associated with Lu. evansi. In this study, OTUs of Methylobacterium found in Lu. evansi was higher in engorged females, suggesting that there are interactions between microbes from plant sources, blood nutrients and the parasites they transmit during the blood intake.